Pengaruh Return on Equity, Debt to Equity Ratio, Net Profit Margin, Inflasi dan Kurs Terhadap Harga Saham Perusahaan Food and Beverage - Marcelina Virdola Agape Zebua; Niniek Imaningsih; Riko Setya Wijaya (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study was conducted to determine the effect of several financial ratios including Return on Equity (ROE), Debt to Equity Ratio (DER), Net Profit Margin (NPM) and macroeconomic indicators including inflation and exchange rates on stock prices of food and beverage companies in the first to fourth quarters of 2017 until 2019. The sample of this study was determined by using purposive sampling technique, in order to obtain PT Delta Djakarta Tbk, PT Indofood Sukses Makmur Tbk, PT Multi Bintang Indonesia Tbk, PT Nippon Indosari Corpindo Tbk and PT. Siantar Top Tbk as research samples from 15 companies listed on the IDX and become the research population. From the data collected, multiple linear regression analysis was carried out using the IBM SPSS Statistics 26 software. From the test results, it was found that there was an effect of debt to equity ratio and net profit margin on stock prices of food and beverage companies, while there was no effect of return on equity, inflation and exchange rates. on stock prices of food and beverage companies.